ERP systems in higher education - Zörög, Zoltán; Csomós, Tamás; Szűcs, Csaba (Applied Studies in Agribusiness and Commerce, 2012)
In the past few decades data processing and in-company communication has changed significantly. First there were only a few computers purchased at companies, therefore departments developed applications that covered corporate administration which lead to so called isolated solutions. These days with the spread of electronic data processing the greatest problem for companies is not gaining information – since they can be found in all sorts of databases and data warehouses as internal or external information – rather producing information that is necessary in a given situation. What can help to solve this situation? It is informatics, more precisely ERP systems which have substituted software that provided isolated solutions at companies for decades. System based thinking is important in their application beside the fact that only data absolutely necessary for managerial decisions must be produced. This paper points out why we consider practice oriented teaching of ERP systems in higher education important.